Thr164Ile polymorphism of β2-adrenergic receptor negatively modulates cardiac contractility: implications for prognosis in patients with idiopathic dilated cardiomyopathy. Issue 7 (14th June 2007) - Barbato, Emanuele; Penicka, Martin; Delrue, Leen; Van Durme, Frederic; De Bruyne, Bernard; Goethals, Marc; Wijns, William; Vanderheyden, Marc; Bartunek, Jozef
Abstract : Background: β2-adrenergic receptor Thr164 Ile (threonine (Thr) is replaced by an isoleucine ( Ile ) at codon 164) polymorphism was postulated to contribute to lower exercise tolerance and poor prognosis in patients with congestive heart failure. However, heart failure is associated with several abnormalities of β receptor signalling, and underlying mechanisms are not clear. Objectives: To investigate whether Thr164 Ile polymorphism negatively modulates myocardial contractile performance and is associated with adverse long-term prognosis of patients with congestive heart failure. Methods: Among 55 subjects, cardiac contractile response to the β2-adrenergic receptor agonist terbutaline was assessed from the peak myocardial velocity of systolic shortening (Sm) in 18 subjects with the Ile -164 variant and 37 matched controls. In total, 24 subjects had normal left ventricular (LV) function and 31 presented with congestive heart failure due to idiopathic dilated cardiomyopathy. Results: In patients with normal LV function, peak terbutaline-induced increase (Δ) in Sm was lower in subjects with the Ile -164 variant than in controls (Δ33% (4%) vs Δ56% (4%), p<0.01). In patients with heart failure, subjects with Ile -164 showed further severe reduction of β2-adrenergic-mediated increase in Sm as compared with controls with heart failure (Δ20% (5%) vs Δ39% (4%), p<0.05). Patients with heart failure with Ile -164 showed a severely blunted force–frequency relationship in response to agonist stimulation. At 2-years of follow-up, patients with heart failure with the Ile -164 variant showed higher incidence of adverse events than controls with heart failure (75% (6/8)] vs 30% (7/23), p<0.05). Conclusions: The β2-adrenergic Thr164 Ile polymorphism directly modulates adrenergic-mediated cardiac responses in patients with normal and failing myocardium. Furthermore, blunted β2 adrenergic-mediated myocardial contractile response in patients with Ile -164 variant seems to adversely modulate the course of congestive heart failure.